Acute Injection of Omega-3 Triglyceride Emulsion Provides Very Similar Protection as Hypothermia in a Neonatal Mouse Model of Hypoxic-Ischemic Brain Injury - Manual Kollareth, Denny Joseph; Zirpoli, Hylde; Ten, Vadim S.; Deckelbaum, Richard J. (Frontiers in Neurology, 2021)
Therapeutic hypothermia (HT) is a currently accepted treatment for neonatal asphyxia and is a promising strategy in adult stroke therapy. We previously reported that acute administration of docosahexaenoic acid (DHA) triglyceride emulsion (tri-DHA) protects against hypoxic-ischemic (HI) injury in neonatal mice. We questioned if co-treatment with HT and tri-DHA would achieve synergic effects in protecting the brain from HI injury. Neonatal mice (10-day old) subjected to HI injury were placed in temperature-controlled chambers for 4 h of either HT (rectal temperature 32C) or normothermia (NT, rectal temperature 37C). Mice were treated with tri-DHA (0.375 g tri-DHA/kg bw, two injections) before and 1 h after initiation of HT. We observed that HT, beginning immediately after HI injury, reduced brain infarct volume similarly to tri-DHA treatment (~50%). Further, HT delayed 2 h post-HI injury provided neuroprotection (% infarct volume: 31.4 ± 4.1 vs 18.8 ± 4.6 HT), while 4 h delayed HT did not protect against HI insult (% infarct volume: 30.7 ± 5.0 vs 31.3 ± 5.6 HT). HT plus tri-DHA combination treatment beginning at 0 or 2 h after HI injury did not further reduce infarct volumes compared to HT alone. Our results indicate that HT offers similar degrees of neuroprotection against HI injury compared to tri-DHA treatment. HT can only be provided in tertiary care centers, requires intense monitoring and can have adverse effects. In contrast, tri-DHA treatment may be advantageous in providing a feasible and effective strategy in patients after HI injury.